Energy saving proposal for UniMAP air-conditioning system - Siti Norhasliza Jamaluddin (School of Electrical Systems Engineering, 2009)
University Malaysia Perlis (UniMAP) is one of the higher learning institutions in Malaysia, located at northern part of Malaysia. This report presented ideas how to reduce amount of energy usage per month and at the same time can save the financial investment for electrical bills specified in air conditioning system. In general, airconditioning system consumes 66% of total electrical peak demand, in its daily activities. These facts show that air conditioning system can contribute a large amount of electricity. Nowadays there are a lot of ideas how to save energy for air conditioning system. In this report presented the explanation about three methodologies that used during the project, which are: 1. Review Technical Installation 2. Install energy saving devices 3. Room calculation Those methods is proposed and reviewed in order to save the energy from the airconditioning system at UniMAP. The calculation and experimental result based on this method are also presented. All the experiment was carried out at UniMAP campus area. In overall, based on the experiment result and the data from the survey, it shows that these, three proposed method can improve the efficiency of the air- conditioning system and at the same time save the energy.